University Teachers’ Perceptions Towards Health and Physical Education - Adhikari, Yadav Raj (Education and Development, 2024)
Health and Physical Education (HPE) is the crucial area of health promotion and quality life. This study aims to explore the teachers’ perceptions towards HPE. To achieve the research objectives, narrative research design following qualitative approach was used. Seven teachers teaching HPE at B.Ed. level were selected purposively from Prithvi Narayan (PN) Campus Pokhara. Information was gathered using unstructured interview. This study reveals that, though HPE is crucial area of teacher education (TE) to prepare quality manpower in the field of health promotion and disease prevention, less priority is given in school level curriculum and the number of students is decreasing in B.Ed. level, therefore, it is in crisis gradually. The existing practices are not supporting for its acceptability and sustainability. There is not a position for HPE teacher in schools and Teachers Service Commission (TSC) does not announce the vacancies for HPE teachers. Teachers, students, curriculum and employability are responsible for this phenomenon. The findings of this study will be useful to policymakers, professionals, students and other stakeholders to take necessary steps for improving the present phenomena.